IMPLEMENTATION OF THE PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENTS' INTERPERSONAL INTELLIGENCE - Siregar, Irayanti; Anhar, Anhar; Azizan, Nashran (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research is encouraged by the low interpersonal intelligence of students in the Pancasila Education subject in class IV MIN 1 Padangsidimpuan City. This is based on data from the results of initial observations conducted in class IV of State Islamic Elementary School (Madrasah Ibtidaiyah Negeri) MIN 1 Padangsidimpuan City. The low interpersonal intelligence of students is caused by the application of learning models that are less effective and varied, as well as less student involvement during the learning process, so that the learning atmosphere feels monotonous and boring. The purpose of this study is to improve students' interpersonal intelligence in the Pancasila Education subject through the application of the Problem Based Learning model in class IV MIN 1 Padangsidimpuan City. The average pre-cycle class score is 59.42 and the percentage of completion is 28.57%. Then, in cycle I meeting 1 the average class score is 65.57 with a percentage of completion of 37.14%. In cycle I meeting 2 the average class score is 62.85 with a percentage of completion of 48.57%. Then, in cycle II, meeting 1, the average class score was 67.74 with a completion percentage of 62.85%. In cycle II, meeting 2, the average class score was 76.34 with a completion percentage of 77.14%. This research finished in cycle II, meeting 2 because it had achieved the targeted success indicators.